Is All Phenomenology Presentational? - Peter V. Forrest (Ergo, An Open Access Journal of Philosophy)
This paper is about two questions in contemporary philosophy of mind, which I call the Scope Question and the Marks Question. The Scope Question is this: What kinds of mental states (events or processes) have phenomenal character, and how many different kinds of phenomenal character are there? The Marks Question is this: What are the distinguishing “marks” of the phenomenal, in virtue of which a mental state, event, or process counts as being phenomenally conscious? To make progress on these questions and explore the relationship between the two, I narrow my focus to a particular instance of each, viz. the (scope) question of whether thoughts possess their own phenomenal character and the (marks) question of whether all phenomenal character is presentational. First, I argue that a phenomenology of entertaining thought content, if it exists, is non-presentational. I then argue from the fact that every genuine phenomenal property can be thought about using a phenomenal concept, to the conclusion that all phenomenology is presentational. One implication is that a (standard form of) transparent, proprietary phenomenology of thought does not exist.